Synthesis method and application of C-coated MoSe2 / SnSe2-coated CNT (O) three-layer nano composite heterojunction material

By symbiotically growing MoSe2 and SnSe2 nanosheets on oxidized carbon nanotubes, the MoSe2/SnSe2@CNT(O) composite material is formed, and the energy capacity and cycle stability of the negative electrode material of lithium-ion batteries are solved, and high specific capacity and long cycle stability are achieved.

CN119812272AActive Publication Date: 2025-04-11HUNAN UNIV

Patent Information

Application Number
CN202510003447.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have problems with low energy capacity and cycle stability, especially the theoretical capacity of graphene is low, and the volume expansion of silicon-based, germanium-based and tin-based materials during the cycle process, resulting in structural damage and low electronic conductivity of the property.

Method used

By symbiotically growing MoSe2 and SnSe2 nanosheets on oxidized carbon nanotubes (CNT(O)), the MoSe2/SnSe2@CNT(O) composite material is formed, and the high theoretical capacity and two-dimensional layered structure of MoSe2 and SnSe2 are used to improve the electrochemical performance of the material by combining the conductivity and stability of CNT(O).

Benefits of technology

High specific capacity and long cycle stability were achieved, the first initial discharge specific capacity reached 1765.55mAh g-1, the capacity remained 1125.67mAh g-1 after 100 cycles, and showed significant electrochemical behavior stability under high current density and long cycle conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812272A_ABST
    Figure CN119812272A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of a lithium ion battery negative electrode material, and particularly relates to a synthesis method of a C (at) MoSe2 / SnSe2 (at) CNT (O) material constructed based on an oxygen-doped carbon nanotube CNT (O). MoSe2 and SnSe2 mutually doped nanosheets are loaded on the surface of the CNT (O), so that the volume expansion of the material can be relieved, more active sites can be provided, and higher capacity and better long cycle stability can be obtained. According to the method, molybdenum pentachloride, dihydroxy butyl tin chloride, Se, CNT (O) and ethylene glycol are used as raw materials, and the C-coated MoSe2 / SnSe2-coated CNT (O) nano composite heterojunction material is synthesized through ultrasonic dispersion and a subsequent calcination method. Compared with similar products, the product obtained by the method has the advantages that the steps are simple, the safety is high, the cost is low, the prepared product nanosheet has obvious morphological characteristics, CNT (O) coated inside provides multiple active sites, the capacity is high, the cycling stability is good, the advantages are obvious under large current (30Ag <-1 > current density, 10000 times of long circulation, and the capacity is kept at 667mA h g <-1 >), and the preparation method is suitable for industrial production. The large-scale production is favorably realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanocomposite material preparation, and relates to the synthesis of a MoSe2 nanosheet and a SnSe2 nanosheet co-grown on a CNT(O) to form a MoSe2 / SnSe2@CNT(O) composite material, which is applied to the negative electrode of a lithium ion battery. Background Art

[0002] Lithium-ion batteries have high energy density, high voltage platform and long cycle life, and are one of the most mature and widely used electrochemical energy storage technologies.

[0003] The negative electrode materials of lithium-ion batteries include carbon materials, such as graphene (whose theoretical capacity is 372mAh / g) and non-carbon materials, such as silicon-based materials, molybdenum-based materials, tin-based materials, nitrides, etc. With the development of science and technology, the theoretical capacity of graphene is low and can no longer meet practical applications. Although silicon-based, germanium-based and tin-based alloy anodes have the advantages of abundance, relatively low lithiation voltage and high lithium reserves, the huge destructive effect of volume expansion during the cycle and low inherent electronic conductivity hinder the further application of these alloy anodes. In order to solve the problems of low energy capacity and cycle stability, it is crucial to develop new high-capacity and low-cost electrode materials.

[0004] Both MoSe2 and SnSe2 belong to transition metal chalcogenides and have been widely studied for their high specific capacity, excellent rate performance and similar two-dimensional layered structure. MoSe2 is a compound with a sandwich structure. It relies on Se-Mo-Se covalent bonds in the plane and weak van der Waals force coupling between layers, which can provide channels for atoms to freely embed and extract between layers. MoSe2 has a special layered structure similar to graphite, with an interlayer spacing of about 0.647nm. The strong metallic properties of MoSe2 can effectively reduce the Gibbs free energy when the material undergoes structural transformation, which is conducive to the insertion and extraction of lithium ions between layers, thereby having stronger electrochemical activity and showing great potential in the field of lithium-ion batteries. The theoretical capacity of pure MoSe2 is 422mAh / g. However, in application, the influence of various factors such as material conductivity, volume expansion, electrolyte stability, etc. will reduce the actual capacity. People usually improve the lithium storage performance of MoSe2 by constructing heterojunctions, element doping, material composites, etc., so that it is closer to the theoretical capacity.

[0005] Tin-based materials are considered to be new potential materials that may replace traditional graphite anodes due to their high theoretical capacity (Sn / SnO / SnO2, 994 / 875 / 1494mAh / g) and natural abundance. However, pure Sn-based materials also have problems such as high volume expansion rate and poor cycle stability. Combining transition metal elements Mo with Sn to form a binary alloy system is an effective material modification strategy. This Sn / Mo binary alloy system has Li provided by the transition metal. + The good ductility of the transition metal can reduce the volume expansion during the lithiation process and cause the structural collapse, so that it can have good electrochemical behavior in the high current and long cycle system.

[0006] Studies have shown that the nanometer-scale diameter of carbon nanotubes and the interlaced gaps between carbon nanotubes give carbon nanotubes excellent chemical and physical properties and lithium embedding properties. Therefore, the lithiation / delithiation process has a short travel distance and a small depth, and the polarization degree is small during high-current charge and discharge, which has a significant effect on the improvement of current density and charge and discharge capacity. Specifically, there are several main reasons for the excellent electrochemical performance of CNTs: (1) The high porosity of CNTs makes Li + Able to diffuse in adjacent spaces; (2) Li + It can be embedded in multiple locations such as the diameter of each tube, the tube core, and the gap between tubes; (3) The nanoscale tube wall can accelerate Li + Migration and diffusion from inside and outside of CNTs; (4) The excess energy brought by the hydrogen-carbon ratio limits the bonding between lithium energy and adjacent hydrogen atoms; (5) In carbon nanotubes, lithium layers may form on the outer surface of graphite in microcrystals; (6) Li + In addition, the excellent conductivity of CNTs can also improve the rapid charge and discharge capabilities of lithium-ion batteries, making them suitable for use as anode materials.

[0007] Based on the above background, MoSe2 and SnSe2 nanosheets are grown on O-doped CNTs to improve the defects of the material's easy expansion and breakage, create more active sites, improve conductivity, and thus improve the electrochemical properties of the material.

[0008] In the present invention, we first synthesized a Mo-based metal complex solution, and then added organic tin to it for further reaction with the metal complex to obtain a Mo-based / Sn-based metal complex mixed solution. After ultrasonic treatment and calcination under an inert gas atmosphere, we successfully prepared a C@MoSe2 / SnSe2@CNT(O) composite material. The product composition was confirmed by X-ray diffraction technology. The prepared C@MoSe2 / SnSe2@CNT(O) product powder was slurry prepared, coated, and dried to obtain an electrode sheet, which was then assembled into a lithium-ion battery as a negative electrode material for electrochemical performance testing. At 0.1Ag -1 At the current density of 1.547 W, the first initial discharge capacity reached 1765.55 mAh g -1 After 100 cycles, the capacity reached 1125.67 mAh g -1 . Increase the test current density to 0.5Ag -1 , 2Ag -1 , 5Ag -1 , 10Ag -1 , 20Ag -1 With 30Ag -1 The initial discharge capacities are 2089.28 mAh g-1 and 1994.45 mAh g-1, respectively. -1 , 1492.75mAh g -1 , 2314.49mAh g -1 , 1909.99mAh g -1 , 1839.89mAh g -1 , indicating that the material has a generally high first specific capacity. It is worth noting that the material shows significant advantages in high current and long cycle. -1 At a current density of 1.34 W, the discharge capacity at the sixth cycle is 600 mAh g -1 After 2000 cycles, the capacity gradually increased to 1205 mAh g -1 After 10,000 long cycles, the capacity remains at 689 mAh g -1 At 30Ag -1 At a current density of 1.34 W, the discharge capacity at the sixth cycle is 530 mAh g -1 After 2500 cycles, the capacity gradually increased to 920 mAh g -1 After 10,000 cycles, the capacity remains at 667 mAh g -1The advantages of high discharge capacity and long cycle life of this material as a negative electrode for lithium-ion batteries can be attributed to the following points. First, the MoSe2 and SnSe2 nanosheets in the system have high theoretical capacity, which can improve the high specific capacity of the composite material. Secondly, MoSe2 nanosheets and SnSe2 are two-dimensional layered materials, which can increase the specific surface area of ​​the composite material and provide Li + The transmission of more nanochannels is improved, and its absorption and desorption capacity in the composite material is enhanced. Thirdly, oxidized carbon nanotubes (CNT(O)) are used as carbon skeletons in composite materials. On the one hand, they can improve the conductivity of the material. On the other hand, the carbon skeleton can enhance the stability of the material and increase the cycle life of the material.

[0009] This invention provides a simple preparation method for the C@MoSe2 / SnSe2@CNT(O) material, which has obvious advantages as anode materials for lithium-ion batteries and provides new ideas for the development of anode materials for lithium-ion batteries. Summary of the invention

[0010] The purpose of the present invention is to develop a high-performance lithium-ion battery negative electrode material, and propose a synthesis method of C@MoSe2 / SnSe2@CNT(O) material based on CNT(O).

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] 1. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) based on CNT(O), the preparation method of the composite material comprising the following steps:

[0013] S1. First, a certain amount of molybdenum pentachloride is added to an ethylene glycol solution to form a molybdenum-based metal organic complex. The best effect is: adding 15-25 ml of ethylene glycol. After the molybdenum-based metal organic complex is completely formed, a certain amount of ethylene glycol solution is added thereto, and then dihydroxybutyltin chloride is added to form a tin-based metal organic complex. The best effect is: adding 5-15 ml of ethylene glycol;

[0014] S2, adding CNT(O) to the solution, placing it in an ultrasonic device for ultrasonication, so that the nanotubes are evenly dispersed and the molybdenum-based / tin-based organic metal complex is evenly adsorbed on the surface of the CNT(O);

[0015] S3, taking out the above solution and placing it in a ceramic ark filled with selenium powder, and then transferring it to a tubular furnace containing Ar atmosphere for calcination at a heating rate of 4-6°C / Min;

[0016] S4. After ultrasonic and calcination reactions, the Mo and Sn elements in the precursor dispersion are in situ selenized into MoSe2 and SnSe2, and the organic components are in situ converted into carbon materials. CNT(O) is coated inside by these three components to obtain C@MoSe2 / SnSe2@CNT(O) nanocomposite materials.

[0017] 2. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs according to claim 1, characterized in that in S1, ethylene glycol is added in portions, and dihydroxybutyltin chloride is added while stirring;

[0018] 3. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs according to claim 1, characterized in that the concentration of molybdenum pentachloride in S1 is 0.01-0.03 mmol mL -1 ;

[0019] 4. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs according to claim 1, characterized in that the concentration of dihydroxybutyltin chloride in S1 is 0.005-0.02 mmol mL -1 ;

[0020] 5.; According to a method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs in claim 1, it is characterized in that in S1, the molar ratio of molybdenum pentachloride to dihydroxybutyltin chloride is 2 to 1;

[0021] 6. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs according to claim 1, characterized in that the concentration of selenium in S1 is 0.08-0.1 mmol mL -1 ;

[0022] 7. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs according to claim 1, characterized in that the concentration of CNT(O) in S2 is 0.4-0.6 mg mL -1 ;

[0023] 8. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNTs according to claim 1, characterized in that in S2, ultrasound is applied for 2 to 4 hours to enhance the dispersion effect of CNT(O);

[0024] 9. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on O-doped CNT structure according to claim 1, characterized in that in S3, the protective atmosphere used is argon, which is maintained at 60-100°C for 3-5h, then heated to 130-300°C and maintained for 3-5h, and finally heated to a calcination temperature of 800°C for 4h, and then naturally cooled to room temperature;

[0025] 10. According to the method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT structure as described in claim 1, it is characterized in that in S4: the composite material is a product C@MoSe2 / SnSe2@CNT(O) nano three-layer composite heterojunction material, MoSe2 and SnSe2 nanosheets are doped and grow around CNT(O), and the carbon layer formed after the carbonization of organic matter is coated on the surface of MoSe2 and SnSe2 to form a carbon layer-transition metal dichalcogenide nanosheet layer-carbon nanotube layer three-layer heterojunction structure, and the carbon nanotube layer can increase the conductivity and stabilize the structure.

[0026] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0027] The present invention uses molybdenum pentachloride, dihydroxybutyltin chloride, Se, CNT(O), and ethylene glycol as raw materials, and prepares C@MoSe2 / SnSe2@CNT(O) nanocomposite three-layer heterojunction material by stirring, ultrasonic dispersion, and high-temperature annealing under inert gas. Compared with similar products, this method has a simple preparation process, and the product performs well in electrochemical tests, with high discharge specific capacity and long cycle stability (at 30Ag -1 At the current density, it reaches 920mAh g after 2500 cycles. -1 High discharge capacity; after 10,000 cycles, there is still 667mAh g -1 , which is close to the initial discharge specific capacity), providing a feasible way for the large-scale production of advanced negative electrode materials for lithium-ion batteries. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned features, advantages and purposes of the present invention more clear and easy to understand, the content of the present invention is further described in detail below in conjunction with specific embodiments. Many specific details are set forth in the above description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.

[0029] The reaction raw materials and catalysts involved in the following examples, unless otherwise specified, are conventional commercially available reagents on the market.

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0031] In Example 1, a C@MoSe2 heterojunction composite material is constructed and its lithium storage performance is studied. The preparation method of the composite material includes the following steps:

[0032] S1, take 150-170 mg of molybdenum pentachloride and dissolve it in 15-25 mL of ethylene glycol to generate a molybdenum-based metal organic complex;

[0033] S2, ultrasonically treating the molybdenum-based metal organic complex solution for four hours until the solution is uniform;

[0034] S3, taking out the above solution and placing it in a ceramic ark containing 130-150 mg of Se powder, then transferring it to a tube furnace containing Ar atmosphere and heating it in stages at 80°C, 180°C, and 800°C, respectively, for 4 hours, with a heating rate of 5°C / min;

[0035] S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized into MoSe2, and the organic components are in situ converted into carbon materials, ultimately generating C@MoSe2 nanocomposite heterojunction materials.

[0036] 2. Further study of the structure of the C@MoSe2 heterojunction composite material and its lithium storage performance required above, characterized in that, in S1, the temperature during the addition process is room temperature.

[0037] 3. Further study of the structure of C@MoSe2 heterojunction composite material and its lithium storage performance required above, characterized in that the composite material is a product C@MoSe2, which is a heterojunction structure in which carbon is coated on the surface of MoSe2, and MoSe2 is a few-layer nanosheet structure.

[0038] 4. Further, C@MoSe2 nanocomposite heterojunction material, acetylene black, and carboxymethyl cellulose (CMC) were mixed and ground in a mass ratio of (4:1:1) and transferred to a volumetric flask, to which water and ethanol were added, and the mixture was thoroughly stirred and evenly mixed, and then coated on a copper foil, dried, and cut to obtain a working electrode.

[0039] In Example 2, a C@SnSe2 heterojunction composite material is constructed and its lithium storage performance is studied. The preparation method of the composite material includes the following steps:

[0040] S1. Take 60-80 mg of dihydroxybutyltin chloride, stir and add 10 mL of ethylene glycol to generate a tin-based metal organic complex;

[0041] S2, stirring the solution for 4 hours to completely dissolve the dihydroxybutyltin chloride in the ethylene glycol, and then transferring the solution to an ultrasonic device for ultrasonication;

[0042] S3, taking out the above solution and placing it in a ceramic ark containing 60-80 mg of Se powder, then transferring it to a tube furnace containing Ar atmosphere and heating it in stages at 80°C, 180°C, and 800°C, respectively, for 4 hours, with a heating rate of 5°C / min;

[0043] S4. After ultrasonic and calcination reactions, the Sn element in the precursor dispersion is in situ selenized to SnSe2, and the organic components are in situ converted into carbon materials, ultimately generating C@SnSe2 nanocomposite heterojunction materials.

[0044] 2. A further method for synthesizing a C@SnSe2 heterojunction composite material according to the above requirement is characterized in that in S1, the temperature during the adding process is room temperature, i.e., 20 to 30°C;.

[0045] 3. Further research on the construction of C@SnSe2 heterojunction composite materials and their lithium storage performance required above is characterized in that the composite material is a product C@SnSe2, which is a heterojunction structure in which carbon is coated on the surface of SnSe2, and SnSe2 is a few-layer nanosheet structure.

[0046] 4. Further, the obtained C@SnSe2 heterogeneous composite material was mixed with acetylene black and carboxymethyl cellulose (CMC) in a mass ratio of 4:1:1, ground and transferred to a volumetric flask, water and ethanol were added thereto, the mixture was fully stirred and evenly mixed, and then coated on a copper foil, dried and cut to obtain a working electrode.

[0047] In Example 3, a C@MoSe2 / SnSe2 heterojunction composite material is constructed and its lithium storage performance is studied. The preparation method of the composite material includes the following steps:

[0048] S1. Take 150-170 mg of molybdenum pentachloride and dissolve it in 15-25 mL of ethylene glycol to form a molybdenum metal organic complex, then add 90-110 mg of dihydroxybutyltin chloride with stirring, and add 5-15 mL of ethylene glycol solvent to the above solution, and wait for sufficient reaction to form a tin-based metal organic complex;

[0049] S2, stirring the solution for 4 hours to completely dissolve the dihydroxybutyltin chloride in the ethylene glycol, and then transferring the solution to an ultrasonic device for ultrasonication;

[0050] S3, taking out the above solution and placing it in a ceramic ark containing 210-230 mg of Se powder, then transferring it to a tube furnace containing Ar atmosphere and heating it in stages at 80°C, 180°C, and 800°C, respectively, for 4 hours, with a heating rate of 5°C / min;

[0051] S4. After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, the Sn element is in situ selenized to SnSe2, and the organic components are in situ converted into carbon materials, ultimately generating a C@MoSe2 / SnSe2 nanocomposite heterojunction material.

[0052] 2. A further method for synthesizing a C@MoSe2 / SnSe2 heterojunction composite material according to the above requirements is characterized in that in S1, the temperature during the addition process is room temperature, i.e., 20 to 30°C;.

[0053] 3. Further, a method for synthesizing a C@MoSe2 / SnSe2 heterogeneous composite material according to the above requirements is characterized in that: the composite material is a product C@MoSe2 / SnSe2 which is a carbon-coated composite nanosheet material, that is, MoSe2 and SnSe2 nanosheets grow together, and carbon is coated on the surface of MoSe2 and SnSe2 nanosheets during calcination to form a carbon composite material.

[0054] 4. Further, the obtained C@MoSe2 / SnSe2 heterogeneous composite material was mixed with acetylene black and carboxymethyl cellulose (CMC) in a mass ratio of 4:1:1, ground and transferred to a volumetric flask, water and ethanol were added thereto, stirred and mixed thoroughly, and then coated on a copper foil, dried, and cut to obtain a working electrode.

[0055] In Example 4, a synthesis method of C@MoSe2 / SnSe2@CNT(O)-based composite material and related lithium storage performance research are provided. The preparation method of the composite material comprises the following steps:

[0056] S1, take 150-170 mg of molybdenum pentachloride and dissolve it in 15-25 mL of ethylene glycol, after the reaction is complete by ultrasonication for 20-40 minutes, add 60-80 mg of dihydroxybutyltin chloride while stirring, and add 5-15 mL of ethylene glycol, stir until the reaction is sufficient to form a mixed solution of molybdenum-based metal complex and tin-based metal complex;

[0057] S2, add 10-30 mg CNT(O) to the solution and sonicate for four hours until it is evenly dispersed;

[0058] S3, taking out the above solution and placing it in a ceramic ark containing 210-230 mg of Se powder, then transferring it to a tube furnace containing Ar atmosphere and heating it in stages at 80°C, 180°C, and 800°C, respectively, for 4 hours, with a heating rate of 5°C / min;

[0059] S4. After ultrasonic and calcination reactions, the Mo and Sn elements in the precursor dispersion are in situ selenized into MoSe2 and SnSe2, and coated and grown on CNT(O), while the organic components are in situ converted into carbon materials and coated on the outer layer of MoSe2 and SnSe2 nanosheets, finally generating C@MoSe2 / SnSe2@CNT(O) three-layer nanocomposite heterojunction material.

[0060] 2. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on CNT(O) according to the above requirements, wherein in S1, the optimal molar ratio of molybdenum pentachloride to dihydroxybutyltin chloride is 2:1;

[0061] 3. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on CNT(O) according to the above requirements, characterized in that, in S1, the temperature during the addition process is room temperature, i.e., 20-30°C;

[0062] 4. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) materials based on CNT(O) according to the above requirements, characterized in that: the composite material is a product of C@MoSe2 / SnSe2@CNT(O) nano three-layer composite heterojunction material (a three-layer heterojunction structure formed by the growth of MoSe2 / SnSe2 nanosheets around CNT(O) and the coating of carbon on the surface of MoSe2 / SnSe2 nanosheets);

[0063] 5. Further, the obtained C@MoSe2 / SnSe2@CNT(O) heterogeneous composite material was mixed with acetylene black and carboxymethyl cellulose (CMC) in a mass ratio of 4:1:1, ground and transferred to a volumetric flask, water and ethanol were added thereto, stirred and mixed thoroughly, and then coated on a copper foil, dried, and cut to obtain a working electrode.

[0064] The following examples 1-4 are used as representatives for characterization:

[0065] The structures of C@MoSe2, C@SnSe2, C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O) were characterized by using SEM and TEM techniques. Figure 2 Figure a shows that C@MoSe2 has a sheet-like structure that interweaves to form a 3D flower-like structure. Figure 2The TEM and HRTEM images in b and c confirm the presence of carbon coating on the MoSe2 structure. It was also observed that the large nanosheets are composed of individual small MoSe2 nanosheets intertwined with each other. In addition, while the MoSe2 nanosheets are surrounded by carbon layers, the number of MoSe2 layers is very small (about 10 layers). Figure 5 The corresponding element diagram in Figure 2 shows the uniform distribution of Mo, Se and C elements in the nanosheet structure, which further confirms that the MoSe2 nanosheets are covered with carbon layers. The formation of few-layer MoSe2 nanosheets is mainly due to the dispersion of Mo-based metal organic complexes by EG, and the organic components in the Mo-based metal organic complexes can serve as carbon sources for the formation of carbon layers. Figure 3 The morphologies of C@MoSe2 (a, d), C@SnSe2 (b, e), and C@MoSe2 / SnSe2 (c, f) are clearly shown. All three are stacked nanosheets. The difference is that the pure MoSe2 and SnSe2 nanosheets are larger in size and easier to agglomerate into clumps, while the C@MoSe2 / SnSe2 nanosheets are more uniform in size and better dispersed. Figure 4 The morphology of C@MoSe2 / SnSe2@CNT(O) is shown. At low magnification, a, b, and c in the figure show that C@MoSe2 / SnSe2@CNT(O) has similar nanosheet morphology to C@MoSe2, C@SnSe2, and C@MoSe2 / SnSe2. The difference is that the smaller and more uniform MoSe2 and SnSe2-doped nanosheets are more compactly attached to the carbon nanotubes. This dense nanosheet structure not only shortens the distance between the inner MoSe2 and the outer carbon surface, but also increases the surface area in contact with the electrolyte. As the lithium ion migration distance is shortened, the utilization rate of the active material will also be improved, thereby improving the battery performance. More specifically, a carbon nanotube extending from the inside of the material appears at the center of c in the figure. After enlarging it, d in the figure can be observed. It can be observed that multiple layers of nanosheets are grown around the CNT(O), confirming that the material structure is a heterojunction structure with internal carbon nanotubes and external nanosheets. Subsequently, HRTEM test was performed to verify the element distribution and content of C@MoSe2 / SnSe2@CNT(O). The EDS-mapping element distribution test results are as follows: Figure 5 As shown in the figure, Mo, Sn, Se, and O are evenly distributed on the material, and the relative content of each element is as follows Figure 5 As shown, the relative content of Mo is 5.08%, the relative content of Sn is 0.13%, and the relative content of Se is 10.44%. It can be seen that the nanosheets attached to the outer layer are mainly MoSe2, with a small amount of SnSe2 doped in them.

[0066] Figure 3The morphologies of C@MoSe2 (a, d), C@SnSe2 (b, e), and C@MoSe2 / SnSe2 (c, f) are clearly shown. All three are stacked nanosheets. The difference is that the pure MoSe2 and SnSe2 nanosheets are larger in size and easier to agglomerate into clumps, while the C@MoSe2 / SnSe2 nanosheets are more uniform in size and better dispersed. Figure 4 The morphology of C@MoSe2 / SnSe2@CNT(O) is shown. At low magnification, Figures a, b, and c show that C@MoSe2 / SnSe2@CNT(O) has similar nanosheet morphology to C@MoSe2, C@SnSe2, and C@MoSe2 / SnSe2. The difference is that the smaller and more uniform MoSe2 and SnSe2-doped nanosheets are more compactly attached to the carbon nanotubes. This dense nanosheet structure not only shortens the distance between the inner MoSe2 and the outer carbon surface, but also increases the surface area in contact with the electrolyte. As the lithium ion migration distance is shortened, the utilization rate of the active material will also be improved, thereby improving the battery performance. More specifically, a carbon nanotube extending from the inside of the material appears in the center of Figure c. After enlarging it, Figure d is obtained, and it can be observed that multiple layers of nanosheets are grown around the CNT(O), confirming that the material structure is a heterojunction structure with internal carbon nanotubes and external nanosheets. Subsequently, HRTEM test was performed to verify the element distribution and content of C@MoSe2 / SnSe2@CNT(O). The EDS-mapping element distribution test results are as follows: Figure 5 As shown in the figure, Mo, Sn, Se, and O are evenly distributed on the material, and the relative content of each element is as follows Figure 5 As shown, the relative content of Mo is 5.08%, the relative content of Sn is 0.13%, and the relative content of Se is 10.44%. It can be seen that the nanosheets attached to the outer layer are mainly MoSe2, with a small amount of SnSe2 doped in them.

[0067] TEM test was performed on C@MoSe2 / SnSe2@CNT(O) to determine the lattice of the material. Figure 7 It can be seen that the material has a very obvious heterojunction structure, with a carbon nanotube mesh structure inside and nanosheets attached to the outside, and has obvious MoSe lattice stripes, which once again verifies the composition and structure of the material.

[0068] According to the SEM and TEM characterization of the four materials, the synthesized materials all have the morphology of stacked nanosheets wrapped in an outer carbon layer, and the heterojunction structure is successfully synthesized. The difference is that the C@MoSe2 / SnSe2@CNT(O) material is filled with an interlaced carbon nanotube structure, which can provide Li + To further understand the material properties, explain Li +The storage mechanism of the material was investigated, and XRD, thermogravimetric, Raman, and XPS analyses were performed to further verify the characteristics of the synthesized material. Figure 8 a shows the XRD images of C@MoSe2, C@SnSe2 and C@MoSe2 / SnSe2@CNT(O). The XRD diffraction technique can clearly show the crystal structure of the material. All peaks in C@MoSe2 represented by purple are consistent with the hexagonal phase of MoSe2 (JCPDS29-0914) with the P63 / mmc space group, indicating that the synthesized material is mainly MoSe2. The C@SnSe2 represented by yellow complies with JCPDS23-0602, while the characteristic peaks of 13.6°, 37.9° and 55.9° in the C@MoSe2 / SnSe2@CNT(O) composite can be well implied on the (002), (103) and (110) planes of hexagonal MoSe2 (PDF#29-0914), and the broad diffraction peak of 11-15°, the strong diffraction peak of 31° and the diffraction peak of 42.1° can be assigned to the (001), (101) and (003) planes of hexagonal SnSe2 (PDF#23-0602). Figure 8 b and 8c are the test results of Raman characterization of C@MoSe2, C@SnSe2, C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O). From the spectra, we can clearly see that the positions of the D peak and the G peak are 1343 cm -1 and 1594cm -1 , Figure 8 c), 1350 and 1580cm -1 The two characteristic peaks on the left and right can reflect the degree of defects in the material, representing the d-bond of disordered carbon and the g-bond of graphene carbon respectively. The d-bond and g-bond strength ratios (ID / IG) of C@MoSe2, C@SnSe2, C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O) composites are all close to 1, among which the ID / IG of C@MoSe2 / SnSe2@CNT(O) is 0.98, indicating that the disordered carbon and graphene carbon components in the C@MoSe2 / SnSe2@CNT(O) composite are roughly equal. In addition, 238cm -1 and 283.1cm -1 They are the out-of-plane (A) 1g ) and in-plane (E 1 2g )'s atomic vibration mode ( Figure 8 c). It can be observed that (A 1g ) and (E 1 2g), which indicates that the carbon outer layer coating will not have a significant impact on the layered structure of MoSe2.

[0069] The surface chemical composition and valence state of C@MoSe2 / SnSe2@CNT(O) composites were studied by X-ray photoelectron spectroscopy (XPS). The full spectrum ( Fig. 9 a) Clearly shows the presence of carbon, oxygen, molybdenum, tin and selenium. Fig. 9 b shows that the C1s peak mainly exists in three forms, 284.8eV represents sp2 CC / C=C, 286.7eV represents CO, and 288.9eV represents C=O. The peaks of Mo, Sn and Se elements in the composite material are shown in Figure 8 d, 8e, and 8f. In the Mo 3d spectrum, 225.7eV and 228.9eV are the Mo 3d5 / 2 and 3d3 / 2 signal peaks, belonging to Mo 4+ The peaks in the Sn 3d spectrum are not obvious, among which the relatively strong 486.7eV and 495.6eV are the Sn 3d5 / 2 and 3d3 / 2 signal peaks, belonging to Sn 4+ The characteristic peak of the Se 3d spectrum is low because the initial addition amount of Sn is relatively small, with a molar amount of only half that of Mo. In addition, the thick C layer coated on the outer layer during the carbonization process also makes the signal peak unclear. In the Se 3d spectrum, the Se 3d peaks at 50.8eV (Se 3d5 / 2) and 51.6eV (Se 3d3 / 2) correspond to Se 2+ state peak.

[0070] To further estimate the carbon content in the samples, thermogravimetric analysis (TAG) was performed on C@MoSe2, C@SnSe2, C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O). Fig.10 As shown in the figure, after being heated in air, MoSe2 and SnSe2 will generate MoO3, SnO2 and SeO2 at 400℃, resulting in a slight increase in weight, and then begin to lose weight at around 400℃, which is caused by the oxidation of carbon materials and the evaporation of SeO2. Among the thermogravimetric curves of the four materials, the thermogravimetric curve of C@MoSe2 / SnSe2@CNT(O) is significantly different from that of the other three materials, indicating that the carbon content, Mo content and Sn content are higher.

[0071] The electrochemical performance of C@MoSe2, C@SnSe2, C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O) is affected by their special nanosheet morphology, bonding mode and composition content. In order to evaluate the lithium storage performance of the materials, they were assembled into button batteries for electrochemical testing. Fig.11 a shows the cyclic voltammogram (CV) curve of the MoSe2 / SnSe2@C electrode as a lithium-ion battery electrode in the initial four cycles in the range of 0.01 to 3.0 V at a scan rate of 0.1 mV s-1. It can be seen from the figure that in the first scan discharge, obvious reduction peaks were observed at 0.90, 0.68, and 0.43 V. The first peak at 0.90 V is Li + Reacts with MoSe2 to convert into Li x The peak at 0.68 V is caused by MoSe2, while the peak at 0.68 V is caused by Li + Insert into SnSe2 layer and alloy reaction occurs to form Na 15 Sn4, while the 0.43 V wide scan peak did not appear in the subsequent discharge process, which may be due to the fact that some Li x MoSe2 is further reduced to Mo and Li2Se, and the electrolyte decomposes to form a solid electrolyte interface (SEI) film. In the subsequent three cycles, reduction peaks were observed at 1.9V and 1.3V, which is due to Li + The further insertion of SnSe2 and the further decomposition of MoSe2 are caused by the further insertion of SnSe2 and the further decomposition of MoSe2. During the charging process, the peaks at 1.4V and 2.1V are caused by the regeneration of MoSe2 and SnSe2. Since the morphology of the subsequent three CV curves is almost overlapping, it can be judged that the C@MoSe2 / SnSe2@CNT(O) material has good reversibility and stability. Fig.11 b shows the CV curves of C@MoSe2 / SnSe2@CNT(O) electrode at different scan rates. These curves have very similar redox peaks, while during the reduction process, as the scan rate increases, the electrode is activated, resulting in a slight shift in the reduction peak. Fig.11 c is the charge and discharge curve of C@MoSe2 / SnSe2@CNT(O). It can be observed from the figure that the discharge capacity gradually decreases with the increase of cycle number, which may be due to the formation of SEI film. Fig.11 d shows the rate performance of C@MoSe2 / SnSe2@CNT(O) as anode material for lithium-ion batteries. -1 Increase to 10Ag -1 , the specific capacity also decreases, at 10Ag -1 At a current density of 1454 mAh g -1 Gradually reduced to 1308, 1138, 960, 921, 893, 836, 761, 732, 686, 534 mAh g -1 When the current density returns to 0.1Ag -1 When the capacity is back to 1491mA hg -1, proving that the material has good rate performance. C@MoSe2, C@SnSe2, C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O) at 0.5A g -1 Cyclic stability and specific capacity at current density Fig.11 As shown in e, the capacity of C@MoSe2 / SnSe2@CNT(O) gradually increased over 150 cycles and finally reached 1505 mAh g -1 , which is significantly better than C@MoSe2 (1105mAh g -1 )、C@SnSe2(376.5mA hg -1 ) , although C@MoSe2 / SnSe2(1235mA hg -1 ) Compared with pure C@MoSe2 and C@SnSe2, the capacity has increased, but it is still lower than that of C@MoSe2 / SnSe2@CNT(O). This is attributed to the heterojunction structure of the MoSe2 / SnSe2 doped nanosheets coated on the outer layer of the C@MoSe2 / SnSe2@CNT(O) material and the oxygen-doped carbon nanotubes CNT(O) wrapped inside, which can provide abundant active sites, and the internal carbon can stabilize the structure and provide material stability. In order to adjust the optimal ratio of MoCl5 and dihydroxybutyltin chloride to obtain the material with the best electrochemical performance, a series of C@MoSe2 / SnSe2@CNT(O) materials were prepared by the same process, and the molar ratio of MoCl5 and dihydroxybutyltin chloride was adjusted to 0.3:0.3, 0.6:0.3, and 0.9:0.3. They were named C@MoSe2 / SnSe2@CNT(O)-1-1, C@MoSe2 / SnSe2@CNT(O)-2-1, and C@MoSe2 / SnSe2@CNT(O)-3-1. The electrochemical performance of the three was tested. At a current density of 0.5A g-1, the specific capacity and cycle stability of the three were as follows: Fig.11 f. After 150 cycles, the discharge capacity of C@MoSe2 / SnSe2@CNT(O)-1-1 is 493.8 mA h g -1 The discharge capacity of C@MoSe2 / SnSe2@CNT(O)-2-1 is 1505.1 mA h g -1 The discharge capacity of C@MoSe2 / SnSe2@CNT(O)-3-1 is 737.2 mAh g -1The optimal input molar ratio is 0.6:0.3. The reason for this phenomenon may be that when the molar ratio is 0.3:0.3, the content of MoSe2, the main contributor to the capacity, is low, resulting in capacity decay. When the molar ratio is 0.9:0.3, although the content of MoSe2 increases, the thickness of the outer layer attached nanosheets also increases, resulting in the stacking of nanosheets, which hinders the transmission of Li+ and reduces the capacity.

[0072] Finally, in order to study the electrochemical performance of C@MoSe2 / SnSe2@CNT(O) under high current density and long cycle, it was used as a negative electrode material for lithium-ion batteries. -1 , 20Ag -1 , 30Ag -1 , the charge and discharge test with a cycle number of 10,000 times, the results are as follows Fig.12 As shown in the figure, it can be clearly seen that the electrochemical behavior of this material is stable at high current density, and the capacity reaches the highest after about 2000 cycles, which is 1308.21 mAh g -1 、1205.78mAhg -1 , 920.14mAh g -1 , and then the capacity steadily decreased. Finally, after 10,000 cycles, the capacity still remained at 655.33 mAh g -1 、689.06mA hg -1 、667.52mAh g -1 , capacity retention rate ~91.1%, 100%, 100%. The reason for its increased capacity and long cycle life may be attributed to the fact that the large current can break through the stacked nanosheets and the intricately crossed nanotube network structure inside, providing more active sites and defects for Li+, thus increasing the capacity, and the carbon nanotubes contained inside can greatly alleviate the volume expansion and extend the battery life.

[0073] At the same time, the thickness of the electrode sheets before and after the cyclic discharge was tested to evaluate the volume expansion of the material. Fig.13 As shown in the figure, it can be observed that the thickness of the electrode sheet before discharge is between 34μm and 39μm, and then increases to 38μm to 40.64μm. It can be seen that the thickness of the electrode sheet does not increase significantly, indicating that the physical structure is relatively stable and the volume expansion is small, which is very beneficial to the stability of the battery.

[0074] In summary, we have demonstrated a simple method to prepare a three-layer C@MoSe2 / SnSe2@CNT(O) three-dimensional nanostructure by in-situ synthesis of MoSe / SnSe using Mo-based organic composites and Sn-based organic composites, and to attach and grow them on oxidized carbon nanotubes. + It provides more active sites and migration channels, and the internal nanotube structure can effectively buffer the volume change of MoSe2 / SnSe2, maintain the stability of the electrode structure, and improve the electron and Li + Ionic conductivity, promoting Li + When used as independent electrodes for lithium-ion batteries, the C@MoSe2 / SnSe2@CNT(O) material provides a high specific capacity (0.5Ag -1 1505mAh g -1 ) and good cycle stability (10Ag -1 Current density 10000 cycles, 655.33 mAh g -1 , 20Ag -1 Current density 10000 cycles 689.06 mAh g -1 , 30Ag -1 Current density 10000 cycles 667.52 mAh g -1 ). The newly developed synthesis method and electrode materials provide a feasible solution for the development of high-capacity and long-cycle negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 .C@MoSe2 / SnSe2@CNT(O) preparation process and structural diagram

[0076] Figure 2 SEM (a) and TEM (b, c) images of C@MoSe2

[0077] Figure 3 .SEM images of C@MoSe2, C@SnSe2 and C@MoSe2 / SnSe2 at different magnifications

[0078] Figure 4 .SEM images of C@MoSe2 / SnSe2 at different magnifications

[0079] Figure 5 .Element distribution of C@MoSe2 / SnSe2@CNT(O) and corresponding EDS-mapping element distribution diagram

[0080] Figure 6.EDS-mapping element content diagram of C@MoSe2 / SnSe2@CNT(O)

[0081] Figure 7 TEM image of C@MoSe2 / SnSe2@CNT(O)

[0082] Figure 8 (a) XRD and (b, c) Raman characterization of C@MoSe2 / SnSe2@CNT(O), and XPS fine spectrum analysis of C@MoSe2 / SnSe2@CNT(O) (d) Mo 3d; (e) Sn 3d; (f) Se 3d

[0083] Fig. 9 .XPS full spectrum (a) and fine spectrum analysis C1s (b) of C@MoSe2 / SnSe2@CNT(O).

[0084] Fig.10 .Thermogravimetric TGA analysis of C@MoSe2, C@SnSe 2, Thermal decomposition process in C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O) composite systems

[0085] Fig.11 .Composite materials C@MoSe2, C@SnSe 2, Lithium storage performance of C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O). (a) Lithium storage performance of the composite material C@MoSe2 / SnSe2@CNT(O) at 0.1 mV s -1 CV curves of the composite material C@MoSe2 / SnSe2@CNT(O) at different scan rates (0.2-1.2 mV s -1 ) under CV curves; (c) charge and discharge curves of the composite material C@MoSe2 / SnSe2@CNT(O); (d) the composite material C@MoSe2 / SnSe2@CNT(O) under 0.1-10Ag -1 Rate performance; (e) C@MoSe2, C@SnSe 2, Cycling performance of C@MoSe2 / SnSe2 and C@MoSe2 / SnSe2@CNT(O) composite materials at 0.5Ag-1

[0086] Fig.12 .Composite material C@MoSe2 / SnSe2@CNT(O) at 10, 20, 30Ag -1 Long cycle performance diagram under high current

[0087] Fig.13In situ SEM analysis changes of C@MoSe2 / SnSe2@CNT(O), (a) charging process from open circuit voltage (OCV) 0.001V to 3.0V, (b) changes after discharge from OCV 3.0 to 0.001V.

Claims

1. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) based on CNT(O), the preparation method of the composite material comprising the following steps: S1. First, a certain amount of molybdenum pentachloride is added to an ethylene glycol solution to form a molybdenum-based metal organic complex. The best effect is: adding 15-25 ml of ethylene glycol. After the molybdenum-based metal organic complex is completely formed, a certain amount of ethylene glycol solution is added thereto, and then dihydroxybutyltin chloride is added to form a tin-based metal organic complex. The best effect is: adding 5-15 ml of ethylene glycol; S2, adding CNT(O) to the solution, placing it in an ultrasonic device for ultrasonication, so that the nanotubes are evenly dispersed and the molybdenum-based / tin-based organic metal complex is evenly adsorbed on the surface of the CNT(O); S3, taking out the above solution and placing it in a ceramic ark filled with selenium powder, and then transferring it to a tubular furnace containing Ar atmosphere for calcination at a heating rate of 4-6°C / Min; S4. After ultrasonic and calcination reactions, the Mo and Sn elements in the precursor dispersion are in situ selenized into MoSe2 and SnSe2, and the organic components are in situ converted into carbon materials. CNT(O) is coated inside by these three components to obtain C@MoSe2 / SnSe2@CNT(O) nanocomposite materials.

2. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S1, ethylene glycol is added in portions, and dihydroxybutyltin chloride is added while stirring.

3. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S1, the concentration of molybdenum pentachloride is 0.01-0.03 mmol mL -1 .

4. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S1, the concentration of dihydroxybutyltin chloride is 0.0005-0.02 mmol mL -1 .

5. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In the S1, the molar ratio of molybdenum pentachloride to dihydroxybutyltin chloride is 2-1.

6. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S1, the concentration of selenium is 0.08-0.1 mmol mL -1 .

7. The method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S2, the concentration of CNT(O) is 0.4-0.6 mg mL -1 .

8. The method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S2, ultrasound was applied for 2 to 4 h to enhance the dispersion of CNT(O).

9. A method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S3, the protective atmosphere used is argon, which is maintained at 60-100°C for 3-5 hours, then heated to 130-300°C and maintained for 3-5 hours, and finally heated to a calcination temperature of 800°C for 4 hours, followed by natural cooling to room temperature.

10. The method for synthesizing C@MoSe2 / SnSe2@CNT(O) material based on O-doped CNT according to claim 1, characterized in that In S4: The composite material is a product of C@MoSe2 / SnSe2@CNT(O) nano three-layer composite heterojunction material, in which MoSe2 and SnSe2 nanosheets are doped and grown around CNT(O), and the carbon layer formed after the carbonization of organic matter is coated on the surface of MoSe2 and SnSe2 to form a carbon layer-transition metal disulfide nanosheet layer-carbon nanotube layer three-layer heterojunction structure, and the carbon nanotube layer can increase the conductivity and stabilize the structure. The preparation process of this method is simple, and the product performs well in electrochemical tests, with high discharge specific capacity and long cycle stability (at 30Ag -1 At the current density, it reaches 920mAh g after 2500 cycles. -1 High discharge capacity; after 10,000 cycles, there is still 667mA hg -1 , which is close to the initial discharge specific capacity), providing a feasible way for the large-scale production of advanced negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of metal organic compound negative electrode material

    CN106848229A

  • Preparation method of carbon-coated tin selenide anode material

    CN108807987A

  • Hydrothermal method for preparing SnSe2 / CNTs composite lithium ion battery electrode material

    CN110190268A

  • Tin diselenide / tin oxide-rGO nano composite negative electrode material and preparation method thereof

    CN111180707A

  • Preparation method and application of graphene@molybdenum diselenide@SnS heterogeneous interface composite material

    CN111916707A

Cited By

  • FeSn sulfide co-doped nanocarbon composite material and preparation method and application thereof

    CN122494617A